2021
DOI: 10.4103/jcn.jcn_171_20
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of Prematurity

Abstract: Purpose: This study aims to estimate the incidence of retinopathy of prematurity (ROP) and investigate its perinatal and neonatal risk factors in a tertiary hospital in Saudi Arabia. Methodology: This was a retrospective cohort study of premature infants admitted to a neonatal intensive care unit at a tertiary hospital in Jeddah, Saudi Arabia, from January 2016 to December 2017. Participants who met the screening criteria for ROP were included and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…21 Additionally, studies from Saudi Arabia reported their prevalence to fall between 21.8% and 33.3%, out of which 80% of the cases resolved spontaneously without any treatment, and only 8.3% of the children received any interventional treatment. 22,23 The rationale for conducting a review article on the prevalence, screening, and treatment of ROP lies in the critical importance of addressing this potentially sightthreatening condition that primarily affects premature infants. ROP is a leading cause of blindness in neonates and given the increasing survival rates of extremely premature babies in neonatal intensive care units, the incidence and significance of ROP continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“…21 Additionally, studies from Saudi Arabia reported their prevalence to fall between 21.8% and 33.3%, out of which 80% of the cases resolved spontaneously without any treatment, and only 8.3% of the children received any interventional treatment. 22,23 The rationale for conducting a review article on the prevalence, screening, and treatment of ROP lies in the critical importance of addressing this potentially sightthreatening condition that primarily affects premature infants. ROP is a leading cause of blindness in neonates and given the increasing survival rates of extremely premature babies in neonatal intensive care units, the incidence and significance of ROP continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, ROP incidence ranges from 23% to 56%. 3 - 7 Preterm infants that are primarily at highest risk for ROP are those with very low birth weight (BW, approximately ≤1500 g) or gestational age (GA, those born at or before 30 weeks). 8 Accordingly, an infant who is smaller or younger at birth is expected to have a greater likelihood of developing ROP.…”
Section: Introductionmentioning
confidence: 99%
“…These factors included mechanical ventilation use, blood transfusion, and poor weight gain (WG) in the initial weeks of life. 3 , 5 …”
Section: Introductionmentioning
confidence: 99%